The Use of Quizlet Application on the Tenth Grade Students’ Vocabulary Mastery at MA Laboratorium UINSU - Annisa Mutiah Matondang; Siti Ismahani (Linguistic, English Education and Art (LEEA) Journal, 2024)
This article aims to determine the effect of using Quizlet application on students’ vocabulary mastery at the MA Laboratory UINSU Medan. The method used is a pre e-experimental design with a quantitative approach. The population that was the research subject was tenth-grade students at MA Laboratorium Uinsu Medan. Consisting of 22 students in it. The researcher gave a pre-test - treatment – and post-test to all samples to collect the required data. After that, the data was processed using the T-test in SPSS.The research findings indicated that the mean pretest score for students was 51.36, whereas the post-test score averaged 83.63. These results indicate a rise in student’s scores from the pre-test to the post-test. It was concluded the implementation of the Quizlet application was found to have a significant impact on student’s comprehension of vocabulary. Keywords: Use, Quizlet Application, Vocabulary Mastery